1982
DOI: 10.1159/000460901
|View full text |Cite
|
Sign up to set email alerts
|

The Serology of Sd^a Effects of Transfusion and Pregnancy

Abstract: Pre- and posttransfusion antibody titers were performed on 6 patients with anti-Sd^a transfused with incompatible blood. In 3 of these patients a significant rise in IgG antibody titer was found. The data suggest that in occasional patients the Sda antigen does evoke a secondary immune response. We evaluated 245 pregnant women for the presence of Sd^a and found that 30% were Sd(a-). This incidence was significantly higher than that found in normal blood donors (4%), but was lower than that described in previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…An increased frequency of Sd(a -) red cell phenotype is found among pregnant women [1,15,21] . In different studies, 36% and 75% were Sd(a -) at term, and 25% six weeks post -partum had Sd(a -) red cells [15,21] .…”
Section: Sd a In Babies And Pregnant Womenmentioning
confidence: 95%
See 2 more Smart Citations
“…An increased frequency of Sd(a -) red cell phenotype is found among pregnant women [1,15,21] . In different studies, 36% and 75% were Sd(a -) at term, and 25% six weeks post -partum had Sd(a -) red cells [15,21] .…”
Section: Sd a In Babies And Pregnant Womenmentioning
confidence: 95%
“…The incidence of anti -Sd a is increased when Sd(a ++ ) cells are used [21] , and the exceptionally strong Sd(a ++ ) Cad cells are agglutinated by most sera. Sd a antibodies are usually IgM and active at 20 o C [1,2,15] , although IgG anti -Sd a has been identifi ed [21,22] .…”
Section: Anti-sd Amentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, human serum anti-Sda antibodies are mainly IgM, 8,9 and anti-Sda IgG antibody titers increase only in patients after the transfusion of Sda-positive erythrocytes. 24 The Tector group's data showed that, after incubation with human serum, knockout of β1,4GalNAcT-II in pig cells decreased the binding of both IgM and IgG. 2,50…”
Section: The Detection Of Sda Antigensmentioning
confidence: 99%
“…(1) Represents a polylactosamine type 2 chain, which is only one of the several Sda active sugar chains reported to date. (2) Two reported Cad structures (in glycophorin and sialylparagloboside), but are not However, if "super Sda" erythrocytes (Cad erythrocytes) are used to detect antibody in the serum, most sera can agglutinate these cells 24. Two cases of hemolytic transfusion reactions related to Cadexpressing RBCs have been reported 27.…”
mentioning
confidence: 99%